SCFFbxw5 targets kinesin-13 proteins to facilitate ciliogenesis - Schweiggert, Jörg; Habeck, Gregor; Hess, Sandra; Mikus, Felix; Beloshistov, Roman; Meese, Klaus; Hata, Shoji; Knobeloch, Klaus-Peter; Melchior, Frauke (The EMBO journal, 2021)
Microtubule depolymerases of the kinesin-13 family play important roles in various cellular processes and are frequently overexpressed in different cancer types. Despite the importance of their correct abundance, remarkably little is known about how their levels are regulated in cells. Using comprehensive screening on protein microarrays, we identified 161 candidate substrates of the multi-subunit ubiquitin E3 ligase SCFFbxw5 , including the kinesin-13 member Kif2c/MCAK. In vitro reconstitution assays demonstrate that MCAK and its closely related orthologs Kif2a and Kif2b become efficiently polyubiquitylated by neddylated SCFFbxw5 and Cdc34, without requiring preceding modifications. In cells, SCFFbxw5 targets MCAK for proteasomal degradation predominantly during G2 . While this seems largely dispensable for mitotic progression, loss of Fbxw5 leads to increased MCAK levels at basal bodies and impairs ciliogenesis in the following G1 /G0 , which can be rescued by concomitant knockdown of MCAK, Kif2a or Kif2b. We thus propose a novel regulatory event of ciliogenesis that begins already within the G2 phase of the preceding cell cycle.